Diagnosis of breast cancer using skin surface electropotentials - Hee, Lily Li Li. (2010)
Breast cancer is the most common cancer in women in Singapore. The current screening techniques have limitations in detecting early stage breast cancer, especially in younger women. Hence, there is a need to develop an efficient, cost-effective screening technique so that the number of affected women can be reduced.